Detection of honey adulteration by conventional and real-time PCR. (January 2019) - Sobrino-Gregorio, Lara; Vilanova, Santiago; Prohens, Jaime; Escriche, Isabel
Abstract: This work applies both conventional and real-time PCR DNA amplification techniques for detecting and quantifying rice molasses in honey. Different levels of adulteration were simulated (1, 2, 5, 10, 20, 50%) using commercial rice molasses. Among the different specific genes of rice tested by PCR, the PLD1 primer was the most effective. This allowed the visualization in agarose gel of this type of adulterant up to 5–20%. Moreover, by means of real-time PCR it was possible to distinguish the different levels of rice DNA, and therefore the percentage of adulteration (1–50%). A standard curve built with the DNA serial dilutions of rice genomic DNA concentrations showed that the quantification level was between 2 and 5%. These results offer compelling evidence that DNA techniques could be useful not only for the detection of adulterations of honey with rice molasses but also for the quantification of levels lower than those of conventional techniques. Highlights: PCR can be applied to detect and quantify the presence of rice molasses in honey. PLD1 was the most effective primer for conventional PCR and RT-PCR. RT-PCR distinguishes different levels of molasses rice added to honey. PCR technique is the best approach in detecting lower levels of adulteration.